Economic relations between Russia and Syria: investments, commodity turnover and prospects - A. H. Eid (Вестник университета)
This article explores the economic relations between the Russian Federation and the Syrian Arab Republic, considers Russian investments in Syria, and analyses the trade turnover. Based on the results of the study and the current geopolitical situation, the prospects for the development of economic relations between the two countries are shown. Using methods of analysis, comparison and a historical approach, the author has concluded that economic relations between Russia and Syria, although quantitatively insignificant, have great prospects for development. One of the prerequisites for the development of trade between Russia and Syria is the pressure of sanctions on these countries. Commodity turnover between these countries is characterised by a much larger flow in one direction – to Syria, which is not surprising, as Syria has been under sanctions since 2011 and is still on its way to economic recovery.